The dose-effect and clinical prediction of the longest apnea duration driving the decrease of blood oxygen: a large sample OSA study with 34-second and 52-second cut-off values was established - Zhou, Xiaobo; Gao, Simin; Zeng, Ping; Li, Lin (Frontiers in Physiology, 2026)
ObjectiveTo quantify the relationship between the longest apnea duration (LAD) and the lowest oxygen saturation (LSaO2) in patients with obstructive sleep apnea (OSA) and to develop a predictive model for the risk of LSaO2 decline.MethodsA total of 1716 OSA patients were enrolled and grouped by severity (236 non-OSA, 395 mild, 365 moderate, and 720 severe). Multiple linear regression was used to analyze the dose-effect relationship between LAD and LSaO2. A logistic regression model was developed to predict LSaO2 grade, with the dataset partitioned into a training set (n = 1,372) and a testing set (n = 344) using random sampling.Results(1) For every 1-s increase in LAD, LSaO2 decreased by 0.280% (95% CI: −0.291%∼-0.269%) in a univariate model and still decreased by 0.183% (95% CI: −0.197%∼-0.170%) after adjusting for sex, age, BMI, and AHI; (2) Critical points were identified: LSaO2 was 85% when LAD was 34.20 s and 80% when LAD was 52.07 s; (3) The predictive model showed excellent identification performance for severe (AUC = 0.93) and moderate-severe LSaO2 (AUC = 0.96).ConclusionThe study first quantifies the dose-response relationship between LAD and LSaO2 and establishes relevant clinical thresholds. The developed model can accurately identify patients at risk of severe and moderate-severe hypoxia, offering a new tool for individualized intervention.